Халх аялгуу дахь эшлэх үйл үг гэ-ийн үүрэг хэрэглээний тухай - Беньямин Брозиг (Mongolian Studies, 2023)
In this article, I give a concise preliminary overview of the functional range of the Khalkha Mongolian quotative verb ge- that is largely based on 3850 tokens of ge- retrieved from a spoken language corpus. Initially, there will be a brief overview of basic functions, including quotation with ge- as main verb or linker, its function in accommodating ideophones, and metalinguistic reference / naming. Secondly, there will be a discussion of different extended functions, namely such connected to (i) information structure, clause connection and text structuring, (ii) intention and its extensions such as forming purpose clauses, prospectives, and goal-benefactors, (iii) sentence-final stance marking (doubt, disagreement, correction, speaker and addressee surprise, anger), and (iv) arguable miscallenous functions (jussive, functive, reflexive, enumerative).